THE INFLUENCE OF KNOWLEDGE, WORK ENVIRONMENT AND HEAD OF ROOM SUPERVISION ON THE IMPLEMENTATION OF NUTRITION SCREENING THROUGH MOTIVATION AS AN INTERVENING VARIABLE AT MUHAMMADIYAH HOSPITAL BANDUNG - Romanti Surya; Idrus Jusat; Erry Yudhya (Jurnal Cinta Nusantara, 2024)
Nutritional screening is the initial stage in inpatient nutrition services which is very important to be carried out by nurses as health workers who first contact with patients and is a simple and quick process with the aim of identifying individuals who are at risk of nutritional problems, so that with good nutritional screening nurses can find out quickly if patients are at risk of nutritional problems to be given appropriate nutritional care. Knowledge, work environment and supervision of the head of the room are some of the factors that influence the implementation of nutritional screening and motivation as intervening variables. Objectives: The purpose of this study was to analyze the effect of knowledge, work environment and supervision of the head of the room on the implementation of nutritional screening by nurses through motivation as an intervening variable in Muhammadiyah Hospital Bandung partially and simultaneously. Method: The research method used is a quantitative method with the type of explanatory causality research. The population in this study is the entire inpatient nurse as many as 150 people. The sample method used was purposive sampling using G-Power application was 71 people. Data analysis method used is multiple linear regression analysis with SPSS software version 21. Result: The results showed that knowledge, work environment and supervision of the head of the room have a significant effect on the implementation of nutritional screening by nurses through motivation as an intervening variable in Muhammadiyah Hospital Bandung. Implication: high knowledge will have a good attitude in implementing nutritional screening with high motivation. Conclusion: knowledge, work environment, head of room supervision and motivation significantly affect the implementation of nutritional screening with a total contribution of 61%. Keywords: Knowledge, Work Environment, Head of Nurse Supervision, Motivation, Implementation Of Nutritional Screening